Optimizing Nasa Liquid Organic Fertilizer Concentration and NPK Fertilizer Dosage 16-16-16 on the Growth and Yield of Glutinous Corn (Zea mays ceratina L.) - Firda Aisha Salsabila; Djarwatiningsih; Didik Utomo Pribadi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Glutinous corn (Zea mays ceratina L.) is a distinctive variety known for its unique starch characteristics and high economic value. One of the challenges affecting glutinous corn plants' productivity is the soil's low nutrient content. To address this issue, improving the fertilization system is essential, which can be achieved by balancing the application of chemical fertilizers and organic fertilizers within the cultivation system. This study aims to identify the optimal doses of liquid organic fertilizer and NPK 16-16-16 fertilizer to enhance crop yields and improve fertilization efficiency. The research employed a factorial randomized block design (RAK) with two factors. The first factor is the dose of liquid organic fertilizer (C), which includes the following levels: control (without POC), 2 ml/l, 4 ml/l, and 6 ml/l. The second factor consists of the control (recommended dose of 4.5 g/plant) and doses of 2.25 g/plant, 3 g/plant, and 3.75 g/plant. Reason: Improved clarity, readability, and technical accuracy while maintaining the original meaning. The results indicated an interaction between the combination of liquid organic fertilizer and NPK 16-16-16 fertilizer treatments concerning the sugar content of glutinous corn. The treatment without applying liquid organic fertilizer (0 ml/l) yielded the highest cob weight without husks, measuring 211.22 g. Additionally, the application of NPK 16-16-16 fertilizer resulted in glutinous corn's most significant plant height at both 14 and 42 days after planting (DAP). It contributed positively to the sugar content of the corn.